Trypanocidal drug screening on Trypanosoma (Dutonella) vivax in vitro - Waithaka, H.K.; Borowy, N.K.; Gettinby, George; Scott, J.; Hirumi, H. (OAU/STRC, 1988)
Technical advances in the continuous cultivation of trypanosomes have enabled the Development of in vitro drug screening techniques. Using the mammalian feeder layer cell system for cultivation of infective haematozoic trypomastigotes of Trypanosoma brucei brucei, significant differences in the sensitivity of trypanosomes to Naganol\A9 and Antrycide\AE were detected to two drug susceptible T. b. brucei clones (Tc 221 and IL 2183) while no differences were detected with Berenil\AE, Samorin\A9, Novidiuin\AE and Arsobal\AE. Further tests were carried out on a total of 21 potential trypanocides which showed varying activities but with compound sinefugin showing the most potent activity in vitro: Simplification of the assay has recently been made using a feeder layer free system. The assay may thus be of potential use for rapid detection of drugresistant isolates. An in vitro technology for supporting the complete cyclic Development of T. vivax has enabled the Development of a drug screening technique for T. vivax. Haematozoic trypamastigotes that have undergone cyclic transformation in vitro should be used for screening trypanocides. However, trypanosome populations isolated directly from infected animal could also be used with certain limitations. The test was performed on 24-well culture plates on to which 1 x 10; viable feeder layer cells/well were seeded 24 hours prior to the test. Trypanosomes (2 x 105/well) were placed into the wells and exposed to drugs for 24 hours at 37\B0C. The activity of each compound was expressed as the effective concentration required to inhibit parasite growth by 50\B0/0 , within a 24 hour exposure period (ICS"). For statistical evaluation of the nested group design, a specific computer program (TRAYCON I) has been developed. The IC0" estimates and 95% confidence intervals were obtained from dose response Logit analysis using maximum likelihood estimation. Seven trypanocides previously tested on T. brucei (TC 221) were screened against T. vivax (IL 1392). Results showed a higher activity against T. vivax than T. brucei by phenanthridines (Samorin\AE and Novidium\AE). The diamidines (Berenil\A9 and pentamidine\AE) were basically similar for both species but napthalenes (Naganol\AE) and quinoldine (Trypanocide\A9) showed much higher activity against T. brucei than T. vivax. The sensitivity and reproductivity observed demonstrated the technique's applicability as a tool for an in vitro search of drugs with specific activity against T. vivax.